Case report: Rhabdomyolysis in children in acute and chronic disease—a challenging condition in pediatric emergency medicine - Mand, N.; Donath, C.; Leonhardt, A.; Weber, S.; Kömhoff, M. (Frontiers in Pediatrics, 2023)
Rhabdomyolysis is a challenging condition in pediatric emergency departments (PED): It ranges from asymptomatic illness with isolated elevation of creatine kinase (CK) levels to a life-threatening condition associated with extreme elevations in CK, electrolyte imbalances, circulatory failure (CF), acute kidney injury (AKI), and multi-organ disease. Most common causes of rhabdomyolysis are viral myositis and trauma, hereditary metabolic myopathies must be considered when facing rhabdomyolysis in early childhood. We report two cases of severe rhabdomyolysis with CF in our PED, thereby summarizing first-line management of rhabdomyolysis.